Differentiation of vaginal cells from epidermal cells using morphological and autofluorescence properties: Implications for sexual assault casework involving digital penetration. (December 2022) - Ingram, Sarah; DeCorte, Arianna; Philpott, M. Katherine; Moldenhauer, Taylor; Stadler, Sonja; Steinberg, Cory; Millman, Jonathan; Ehrhardt, Christopher J.
Abstract: This work explores morphological and autofluorescence differences between vaginal and epidermal cells detectable through Imaging Flow Cytometry (IFC), a non-destructive, high-throughput technique. These differences were used to build a predictive framework for classifying unknown cells as originating from vaginal or epidermal tissue, which was tested on hand swabbings with and without digital penetration. Many more cells possessing a vaginal signature (median posterior probability ≥0.90) were detected in digital penetration samples than control hand swabbings. Minimum interpretation thresholds were developed to minimize/eliminate false positives; these thresholds were also effective when screening licked hands, indicating the potential utility of this method for a variety of biological mixture types and depositional events relevant to forensic casework.